Sciatica caused by spinal epidural abscess as the initial clinical presentation of colon cancer: a rare case report and review of literature - Kuan-Yu Lu; Wei-En Tung; Chang-Jung Chiang; Yueh-Ying Hsieh; Chia-Hsien Chen; Mei-Hui Lee; Min-Hsuan Yen; Po-Wen Lu; Lien-Chen Wu (BMC Infectious Diseases, 2024)
Abstract Background Colorectal cancer is one of the most frequently diagnosed forms of cancer, and it is associated with several common symptoms and signs such as rectal bleeding, altered bowel habits, abdominal pain, anemia, and unintentional weight loss. Sciatica, a debilitating condition in which the patient experiences paresthesia and pain in the dermatome of associated lumbosacral nerve roots or sciatic nerve distribution, is not considered one of these. Here we present a case of colorectal cancer manifesting symptoms of sciatica alone. Case presentation A 68-year-old male presented with progressive lower back pain radiating to his left thigh and calf over L5/S1 dermatome. Sciatica was suspected and initially underwent conservative treatment with analgesics. However, the symptoms progressed and MRI revealed an epidural abscess surprisingly. Surgical debridement was performed and pus culture isolated Streptococcus gallolyticus. Based on the strong association of S. gallolyticus with colorectal cancer, the presence of this pathogen prompted further tumor evaluation, even in the absence of the typical symptoms and signs. This investigation ultimately leads to the diagnosis of sigmoid adenocarcinoma. Conclusions Although rare, sciatica caused by S. gallolyticus infection of the spinal epidural space may serve as the initial presentation of colorectal cancer. Physicians should be aware of the strong association between S. gallolyticus and colorectal cancer. Based on what we currently know about the condition; a thorough systematic assessment of occult neoplasia for patients with S. gallolyticus infection is recommended.